1999
DOI: 10.1126/science.286.5447.2162
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Immunoproteasome Assembly and Immune Responses in PA28 −/− Mice

Abstract: In vitro PA28 binds and activates proteasomes. It is shown here that mice with a disrupted PA28b gene lack PA28a and PA28b polypeptides, demonstrating that PA28 functions as a hetero-oligomer in vivo. Processing of antigenic epitopes derived from exogenous or endogenous antigens is altered in PA28-/- mice. Cytotoxic T lymphocyte responses are impaired, and assembly of immunoproteasomes is greatly inhibited in mice lacking PA28. These results show that PA28 is necessary for immunoproteasome assembly and is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
4
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 21 publications
8
106
4
1
Order By: Relevance
“…Alternatively, immunosubunit incorporation could influence the substrate accessibility via the regulatory particles PA700 or PA28ab. Indeed, mice lacking PA28b demonstrated impaired immunosubunit incorporation into 20S proteasomes (44), although these results could not be confirmed in mice lacking both PA28a and PA28b (24). Our results suggest a more simple explanation as to how the structural features of immunosubunits can influence CTL epitope generation.…”
Section: Discussionmentioning
confidence: 60%
“…Alternatively, immunosubunit incorporation could influence the substrate accessibility via the regulatory particles PA700 or PA28ab. Indeed, mice lacking PA28b demonstrated impaired immunosubunit incorporation into 20S proteasomes (44), although these results could not be confirmed in mice lacking both PA28a and PA28b (24). Our results suggest a more simple explanation as to how the structural features of immunosubunits can influence CTL epitope generation.…”
Section: Discussionmentioning
confidence: 60%
“…Immunoproteasomes contain an IFN-g inducible regulatory unit called the proteasome activator PA28 (Rock and Goldberg 1999;Kloetzel 2001). PA28 on its own can influence antigen presentation drastically, mainly by changing the kinetics of the degradation process without altering the specificity (Preckel et al 1999;Stohwasser et al 2000;Van Hall et al 2000;Kloetzel 2001;Sijts et al 2002;Sun et al 2002). Moreover, the immunoproteasomes, unlike constitutive proteasomes, may co-localize with TAP and thus increase MHC class I antigen presentation (Brooks et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these differences are attributable to the absence of LMP7 alone, or are compounded by reduced LMP2 and MECL1 incorporation in LMP7 Ϫ/Ϫ mice (23), is not clear. However, PA28b Ϫ/Ϫ mice have normal class I expression despite a defect in immunoproteasome assembly (42). Interestingly, while LMP2 and MECL1 are not incorporated into proteasomes in these mice, LMP7 is incorporated, albeit at reduced levels.…”
Section: Figmentioning
confidence: 97%
“…A third possibility is that other accessory proteins are involved in immunoproteasome assembly. In this regard, it was recently shown that PA28a and PA28b associate with preimmunoproteasomes, and in the absence of PA28b (PA28b Ϫ/Ϫ mice) recovery of these complexes is reduced, as is the incorporation of immunoproteasome subunits (42). This raises the possibility that the role of PA28 in proteasome assembly may involve binding to the ␣-ring and inducing a conformational change that makes preproteasomes more receptive to LMP2 and/or MECL1.…”
Section: Figmentioning
confidence: 97%